Association between ABO blood type and type I endometrial cancer: a retrospective study - Shiyuan Wei; Tingting Yi; Zhenbo OuYang; Jiawen Wu (Taylor & Francis Group, 2023)
This study aimed to assess the association between ABO blood type and incident of type I endometrial cancer (EC), as well as the stage and differentiation. 213 patients with type I EC and 300 healthy controls were included. As a result, the frequencies of A, B, O, and AB blood types among patients with type I EC were 51 (23.9%), 59 (27.7%), 93 (43.7%) and 10 (4.7%), respectively. There were no significant differences in age, body mass index, and other baseline covariates between groups of ABO blood types (p > .05). Logistic regression model showed that women with blood type O was more likely to develop type I EC than those with type A (odds ratio (OR): 1.66, 95% confidence interval (CI): 1.05-2.63). However, there was no significant association of ABO blood type with stage and differentiation of type I EC (p > .05). In conclusion, blood type O was the most prevalent ABO blood type among patients with type I EC and was associated with increased risk of type I EC, while ABO blood type was not significantly associated with stage or differentiation of type I EC.IMPACT STATEMENT What is already known on this subject? Previous studies have produced inconsistent findings on association of ABO blood type with EC. Those studies also did not explore the relationship between ABO blood type and stage or differentiation of type I EC. What the results of this study add? The present study showed that women with blood type O was more likely to develop type I EC than those with type A and there was no significant association of ABO blood type with stage or differentiation of type I EC. What the implications are of these findings for clinical practice and/or further research? Gynaecologists should pay more attention to women with blood type O, who should undergo more active EC screening.